2008
DOI: 10.1088/1475-7516/2008/05/010
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal processes in standard big bang nucleosynthesis: I. In-flight nuclear reactions induced by energetic protons

Abstract: The standard model of big bang nucleosynthesis (BBN) relies on a nuclear reaction network operating with thermal reactivities for Maxwellian plasma. In the primordial plasma, however, a number of non-thermal processes triggered by energetic particles of various origins can take place. In the present work we examine in-flight nuclear reactions induced in the plasma by MeV protons generated in D(d, p)T and 3He(d, p)4He fusions. We particularly focus on several low threshold endoergic processes. These are reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 43 publications
(122 reference statements)
1
53
0
Order By: Relevance
“…This assertion was based on a paper by Dixit et al [36], which studied 9 Be(p, p), and which identified a strongly excited, and relatively narrow, state at 16.7 MeV. In that paper the possible structure of a narrow state at such high excitation is discussed, and is identified with earlier theoretical work [37] in which this state is suggested as having a structure of an s 1/2 neutron coupled to highly excited 2 + core states in 8 Be. Such states could only be ν…”
Section: A Comments On the Added Nuclear Reaction Ratesmentioning
confidence: 89%
“…This assertion was based on a paper by Dixit et al [36], which studied 9 Be(p, p), and which identified a strongly excited, and relatively narrow, state at 16.7 MeV. In that paper the possible structure of a narrow state at such high excitation is discussed, and is identified with earlier theoretical work [37] in which this state is suggested as having a structure of an s 1/2 neutron coupled to highly excited 2 + core states in 8 Be. Such states could only be ν…”
Section: A Comments On the Added Nuclear Reaction Ratesmentioning
confidence: 89%
“…We will describe the reverse (α, p) process (3) within the in-flight nuclear-reaction formalism used earlier to analyze nonthermal reactions in the early Universe [16] and in superdense laboratory plasmas [17]. The probability W α 14 N that, in the course of deceleration in the plasma, a fast alpha particle undergoes the reaction α…”
Section: Nonthermal Reactions Involving Fast Alpha Particlesmentioning
confidence: 99%
“…In a series of papers [16][17][18]20] we examined the mechanisms and rates of nonthermal processes naturally triggered in the BBN epoch by fast particles generated in the tðd; nÞ, dðd; nÞ 3 He, dðd; pÞt, and 3 Heðd; pÞ reactions. The present work follows up these studies, considering the influence of such processes on the primordial element production.…”
Section: Discussionmentioning
confidence: 99%
“…Let us consider effects caused by nonthermal neutrons (for charged-particle effects, see [16,18]). Reactions having a resonancelike behavior at suprathermal energies and threshold processes are most sensitive to fast neutrons in the plasma.…”
Section: Particlementioning
confidence: 99%
See 1 more Smart Citation